2021
DOI: 10.1002/ece3.7662
|View full text |Cite
|
Sign up to set email alerts
|

Ant community composition and functional traits in new grassland strips within agricultural landscapes

Abstract: This is an open access article under the terms of the Creative Commons Attribution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 60 publications
0
4
0
Order By: Relevance
“…Supporting this, we found that year since prairie strip establishment affected all responses that we measured at distances from prairie strips except ant richness (Figure 4). Lack of response of ant species richness is consistent with other grassland restoration projects where it takes several years for ant communities to turnover (Dauber and Wolters, 2005;Menke et al, 2015;Hussain et al, 2021;Scharnhorst et al, 2021). With the exception of active carbon, variables displayed a general progression of the first year having small to no effect of distance from prairie strip, to the second year showing a stronger negative effect of distance.…”
Section: Discussionsupporting
confidence: 85%
“…Supporting this, we found that year since prairie strip establishment affected all responses that we measured at distances from prairie strips except ant richness (Figure 4). Lack of response of ant species richness is consistent with other grassland restoration projects where it takes several years for ant communities to turnover (Dauber and Wolters, 2005;Menke et al, 2015;Hussain et al, 2021;Scharnhorst et al, 2021). With the exception of active carbon, variables displayed a general progression of the first year having small to no effect of distance from prairie strip, to the second year showing a stronger negative effect of distance.…”
Section: Discussionsupporting
confidence: 85%
“…A recent study conducted in differently structured urban green spaces further indicated that structural complexity of the local vegetation can act as an environmental filter, driving ant communities in terms of species numbers and functional traits (Nooten et al, 2019 ). Comparatively few studies have been conducted in managed temperate grasslands by directly addressing the environment‐community structure relationship at different spatial scales (Dahms et al, 2010 ; Dauber et al, 2003 ; Dauber & Wolters, 2005 ), and even fewer have included a functional trait‐based approach (Heuss et al, 2019 ; Scharnhorst et al, 2021 ; van Noordwijk et al, 2012 ).…”
Section: Introductionmentioning
confidence: 99%
“…While useful in comparing broad community structures, care should be taken to not confound functional groups with having shared functional traits. More recent approaches often correlate trait morphospace with ecology to examine functional diversity (e.g., Nooten et al, 2019 ; Retana et al, 2015 ; Scharnhorst et al, 2021 ). However, conclusions from linking environmental or biological variation to morphological features of the species living there remain tenuous due to untested assumptions about traits and their function (but see Gibb & Parr, 2013 ; Nooten et al, 2019 ; Retana et al, 2015 ).…”
Section: Introductionmentioning
confidence: 99%